Protection against creditors, indemnity and No Claim Benefits (NCB) under life insurance and family takaful - Yusuf Sani Abubakar,; Muhammad Anowar Zahidi,; Ruzian Markom, (Penerbit Universiti Kebangsaan Malaysia, 2016)
This is a doctrinal and comparative research between the traditional law and the Shariah with regard to issues of protection against creditors, indemnity and no claim benefits (NCB) under life insurance and family takaful. The aim is to find similarities and dissimilarities between life insurance and family takaful vis-à-vis the issues based on Maqasid al-Shariah. It is found that both the traditional law and the Shariah assert that creditors have priority over the life policy and family takaful benefits even if the beneficiaries will get nothing from it. Again, under both systems, it is submitted that although ‘Indemnity’ and ‘No claim benefits’ are paid but the Shariah does not allow forfeiture of the indemnity because of lack of utmost good faith (uberimae fidei) or discontinuing payment of the premiums/contributions by the policyholder or participant. It is further submitted that under takaful the No Claim Benefits (NCB) should be paid based on al-Mudarabah agreement and not interest and uncertainty. And all these ensure protection of religion and property.